Orbicular rooms: Spaces that resist panoptic power in the Manuel Rojas' narrative tetralogy - Fuentes Retamal, Pablo (2017)
This article studies the tenement houses detailed in the novels of Manuel Rojas’narrative tetralogy. There are:Hijo de ladron(1951), Mejor que el vino(1958), Sombras contra el muro (1964), y Laoscura vida radiante (1971). The tenements are urban housings that harbor many rooms inside, organized in rows around a central courtyard. This architectural distribution adjusts to the panopticon model designed by Jeremy Bentham. In Rojas’narrative tetralogy some rooms which are inhabited by characters with an anarchist affiliation are described. These constructions, due to their circular distribution, manage to resist the control and discipline mechanisms predicted by the panopticon power